2022
DOI: 10.1021/acsami.2c17242
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Hydrogel Loaded with Nickel–Copper Bimetallic Hollow Nanospheres with SOD and CAT Enzymatic-Like Activity Promotes Acute Wound Healing

Abstract: Various injury defense and repair functions are performed by the skin. Free radicals secreted after injury cause oxidative stress and inflammatory responses, which make wound healing difficult. However, the current metal nanomaterials for wound repair do not have sufficient catalytic activity or complex material design and cannot properly fit wounds. Therefore, it is imperative to develop more effective therapeutic approaches. This study investigated the effect of Ni 4 Cu 2 hollow nanospheres composited with F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Puertas-Bartolomé et al fabricate a catechol-bearing NPs hydrogel and demonstrate that it possesses excellent wound healing capacities, including the regulation of ROS production, an anti-inflammatory response, and the upregulation of VEGF expression [ 117 ]. Similarly, Ni 4 Cu 2 hollow nanospheres, applied in combination with F127 hydrogel, were found to effectively promote wound healing, epithelial regeneration, and the formation of hair follicles in mice [ 118 ]. Moreover, Zhu et al prepared an injectable hydrogel containing substance P-loaded NPs, which showed excellent wound-healing efficacy by promoting an early inflammatory response and the subsequent M2 macrophage polarization in full-thickness wounds [ 119 ].…”
Section: Different Types Of Bioactive Wound Dressings To Modulate Mac...mentioning
confidence: 99%
“…Puertas-Bartolomé et al fabricate a catechol-bearing NPs hydrogel and demonstrate that it possesses excellent wound healing capacities, including the regulation of ROS production, an anti-inflammatory response, and the upregulation of VEGF expression [ 117 ]. Similarly, Ni 4 Cu 2 hollow nanospheres, applied in combination with F127 hydrogel, were found to effectively promote wound healing, epithelial regeneration, and the formation of hair follicles in mice [ 118 ]. Moreover, Zhu et al prepared an injectable hydrogel containing substance P-loaded NPs, which showed excellent wound-healing efficacy by promoting an early inflammatory response and the subsequent M2 macrophage polarization in full-thickness wounds [ 119 ].…”
Section: Different Types Of Bioactive Wound Dressings To Modulate Mac...mentioning
confidence: 99%
“…Hydrogels are three-dimensional (3D) networks formed by cross-linking hydrophilic polymer chains, which are similar to extracellular matrix (ECM) and can provide a moist environment to promote wound healing. , In particular, thermosensitive hydrogels can be applied to different desired wound shapes at body temperature . Alginate is a natural polysaccharide derived from brown seaweed, which can increase the moisturizing effect and improve the mechanical properties of thermosensitive hydrogels .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 In particular, thermosensitive hydrogels can be applied to different desired wound shapes at body temperature. 28 Alginate is a natural polysaccharide derived from brown seaweed, which can increase the moisturizing effect and improve the mechanical properties of thermosensitive hydrogels. 29 Thus, alginate-based thermosensitive hydrogel is a promising biomaterial for wound dressings.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations